2011
DOI: 10.1002/ijc.26221
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid arginine starvation efficiently sensitizes cancer cells to canavanine treatment and irradiation

Abstract: Single amino acid arginine deprivation is a promising strategy in modern metabolic anticancer therapy. Its potency to inhibit tumor growth warrants the search for rational chemo-and radio-therapeutic approaches to be co-applied. In this report, we evaluated, for the first time, the efficacy of arginine deprivation as anticancer therapy in three-dimensional (3D) cultures of human tumor cells, and propose a new combinatorial metabolic-chemo-radio-treatment regime based on arginine starvation, low doses of argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 73 publications
4
45
0
1
Order By: Relevance
“…One such limitation arises from the upregulation of ASS expression in many tumors in response to arginine starvation, leading to the appearance of the ASS-positive tumor relapse insensitive to the therapy (Vynnytska-Myronovska et al, 2012). Also, results showed that tumor cells become profoundly more resistant to arginine withdrawal in in vitro 3D spheroid models relative to respective monolayer cultures (Vynnytska-Myronovska et al, 2013).…”
Section: Combination Therapiessupporting
confidence: 45%
“…One such limitation arises from the upregulation of ASS expression in many tumors in response to arginine starvation, leading to the appearance of the ASS-positive tumor relapse insensitive to the therapy (Vynnytska-Myronovska et al, 2012). Also, results showed that tumor cells become profoundly more resistant to arginine withdrawal in in vitro 3D spheroid models relative to respective monolayer cultures (Vynnytska-Myronovska et al, 2013).…”
Section: Combination Therapiessupporting
confidence: 45%
“…Nevertheless, it has also been found more recently that canavanine could have important therapeutic properties. Thus, canavanine inhibits cell proliferation [20] and induces apoptosis [21,22] in cell cultures, and it also increases susceptibility to radiation in cancer cells [23]. In addition, it inhibits some of the deleterious effects of endotoxic shock in rat models [24,25] and has potential as an antidiabetic agent because it has been found to increase uptake of glucose [26] and release of insulin [27] in cell cultures.…”
Section: Speciessupporting
confidence: 40%
“…In the absence of arginine, canavanine not only induces programmed cell death in cancer cell subpopulations, but also severely interferes with growth recovery of the remaining membrane-intact cells after the termination of treatment [18, 23]. We therefore evaluated the impact of citrulline supplementation on the regrowth potential of arginine-starved, canavanine-treated CRC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, CRC was excluded from the list of tumors defined as the responders to arginine deprivation therapy [4, 7]. However, our recent in vitro data indicate that cancer cells might be radiosensitized in the absence of arginine even if they express citrulline-to-arginine converting enzymes [18, 19]. Therefore, it is reasonable to speculate that arginine deprivation therapy could prime CRC and other ASS1-positive malignancies to both standard-of-care and novel combinational therapies.…”
Section: Introductionmentioning
confidence: 99%